Antifungal Screening of Some Transition Metal Ferrocyanides Against Aspergillus niger and Candida albicans - Bharti, Dipti; Arora, Charu; Kaur, Gurleen (Asian Journal of Chemistry, 2011)
Synthetic and antimicrobial aspects of some clinical pathogen inhibitor transition metal ferrocyanides complexes were carried out. Ferrocyanides of Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) were synthesized by known Kourim's procedure. Antifungal screening of these metal ferrocyanides was carried out against Aspergillus niger and Candida albicans using paper disc and food poisoning technique. Cobalt ferrocyanides showed significant potential activity against A. niger (72 %) and cadmium ferrocyanide showed maximum growth inhibition against C. albicans (85 %) respectively.